Implementasi Culturally Responsive Teaching Berbasis Aplikasi 'BelaJARingan' untuk Meningkatkan Prestasi Belajar dan Pemahaman Budaya Peserta didik SD - Nur Fauzan; Via Yustitia; Daniar Meiliana Rahayu (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This article describes the implementation of the Culturally Responsive Teaching (CRT) approach by utilizing the integrated application "BelaJARingan" at SDN Dukuh Menanggal I/424 Surabaya. This study aims to increase student involvement in the learning process, as well as foster a deeper understanding of culture through contextual learning. This study uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation of the learning process in class 4A SDN Dukuh Menanggal I/424 Surabaya involving 30 students with diverse cultural backgrounds. Data analysis was carried out descriptively by grouping the results of observations and interviews to assess the effectiveness of the application of technology-based CRT in increasing student learning motivation and cultural understanding. By integrating digital technology and local culture, this application allows students to access teaching materials, quizzes, and culture-based projects. The results of the study indicate that this approach not only improves learning achievement but also encourages appreciation for cultural diversity. Despite technical constraints, the technology-based CRT approach has proven effective in creating a more interactive and meaningful learning process for students.